On What Cannot Be Said : Apophatic Discourses in Philosophy, Religion, Literature, and the Arts. Volume 1. Classic Formulations. - Franke, William (University of Notre Dame Press, 2007)
Apophasis has become a major topic in the humanities, particularly in philosophy, religion, and literature. This monumental two-volume anthology gathers together most of the important historical works on apophaticism and illustrates the diverse trajectories of apophatic discourse in ancient, modern, and postmodern times. William Franke provides a major introductory essay on apophaticism at the beginning of each volume, and shorter introductions to each anthology selection. The first volume, Classic Formulations, offers excerpts from Plato, Plotinus, Damascius, the Bible, Gregory of Nyssa, Augu.